Exploration Study of Contemporary Batik Motif at The Handayani Community Learning Center Kemirian Village Tamanan District Bondowoso Regency - Imama, Derrida Dhini; Irianti, Agus Hery Supadmi; Kusumawardani, Hapsari (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The learning center community for public named Handayani is an Small and Medium Enterprise located in Kemirian Village, Tamanan Subdistrict, Bondowoso Regency. PKBM handayani is a non-formal educational institution and also known as a batik business that produces written batik, stamped batik, and semi batik. This study aims to identified any typical Motif of contemporary batik Bondowoso whose produced by PKBM Handayani. This research was using a qualitative descriptive approach with observation, interviews, and documentation both offline and online as the data collection techniques. The result for this research are the identification of nine Motifs of batik which consist by the classification of ornaments and colors, and also the symbols and meanings contained in the Motifs. This research also shows that the role of Bondowoso Regency government has been held well in the development of PKBM Handayani implemented as a facilitator, motivator, and catalyst. The researcher hopes that through this research, PKBM Handayani can be recognized and being widely known by the wider community and also increase its sales and their business development.